Identifying multimorbidity risks in older adults: a cross-sectional study using the RGA screening data - Cho, Jinmyoung; Gibson, Allison; Zubatsky, Max; Wang, Wenjin; Nketsiah, Ebow; Sanford, Angela; Berg-Weger, Marla (Frontiers in Public Health, 2025)
Approximately one in two older adults in the U.S. experiences multimorbidity, defined as the coexistence of two or more chronic diseases. The consequences of multimorbidity are significant, including increased vulnerability to acute illness, exacerbation of existing conditions, frequent hospitalizations, and elevated medical costs. Identifying the risk factors for multimorbidity in advance can guide healthcare service decision-making and help prevent adverse outcomes. This study examines the presence of multimorbidity (i.e., self-reported as having five or more illnesses) and specific geriatric syndromes in older adults with the Rapid Geriatric Assessment (RGA) tool. The RGA, which includes four geriatric syndromes: frailty, sarcopenia, geriatric anorexia, and cognitive decline, was administered to a total of 16,615 individuals aged 65 years and over across Missouri from 2015 to 2024. Nearly 40% of the participants (37.3%) reported having five or more illnesses. After controlling for demographic characteristics, logistic regression analysis showed that individuals with sarcopenia were over three times more likely to have multimorbidity compared to those without sarcopenia (OR = 3.807; CI: 3.488–4.156, p < 0.001). Similarly, the presence of geriatric anorexia and dementia was significantly associated with a 33% (OR = 1.329; CI: 1.224–1.443, p < 0.001) and 27% (OR = 1.273; CI: 1.158–1.401, p < 0.001) higher probability of having multimorbidity, respectively. This cross-sectional study provides evidence that the RGA is a valid screening tool for identifying individuals with multimorbidity across different practice settings. The findings underscore the importance of early detection of geriatric syndromes to prevent further morbidity and disability among older adult populations.